2-4h=6-6h

Simple and best practice solution for 2-4h=6-6h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-4h=6-6h equation:


Simplifying
2 + -4h = 6 + -6h

Solving
2 + -4h = 6 + -6h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '6h' to each side of the equation.
2 + -4h + 6h = 6 + -6h + 6h

Combine like terms: -4h + 6h = 2h
2 + 2h = 6 + -6h + 6h

Combine like terms: -6h + 6h = 0
2 + 2h = 6 + 0
2 + 2h = 6

Add '-2' to each side of the equation.
2 + -2 + 2h = 6 + -2

Combine like terms: 2 + -2 = 0
0 + 2h = 6 + -2
2h = 6 + -2

Combine like terms: 6 + -2 = 4
2h = 4

Divide each side by '2'.
h = 2

Simplifying
h = 2

See similar equations:

| -50+1.0x=300 | | 4x-3=-103-6x | | Y=-4x-16x+20 | | 2x+5-8w=7-4w | | 3m+3-m=3(m+1) | | -1v+5+4v=1+5v+3 | | (2i+3)(7i+6)= | | 9x+6(3x-4)=12-9x | | 3a-11=4(a+1)+13a+3 | | 2g-8+3g=7 | | .17(x+29)=86 | | 2x-6=5x+27 | | 2y^2-7y-10=0 | | 4x-2(.50-1)=14 | | 101(87+13)= | | y^3+729= | | 4x-2(x-2)=-7+4x+5 | | 9x-12=84 | | 4(2x-3)=30 | | 15-12z=21 | | .17(x-29)=86 | | 2x=1-5 | | 7(x+2)=5(x+14) | | p-4=-1+2P | | 4m+8m=84 | | 2(m-8)=12 | | 9k(8k+7)= | | 10x+44=2(8x-23) | | T+4=120 | | 10-2x=-2y | | 77x^2-145+50= | | 9(x-7)+54=9x-8 |

Equations solver categories